Mechanical design of gear train efficiency test rig - Efficiency evaluation of geared front attachments in industrial tightening tools - Shin, Miranda (My University, 2024)
Atlas Copco desires a test rig where they can perform gear accuracy and efficiency tests with the aim of potentially enhancing the performance of their Geared Front Attachment (GFA) tool tightening solutions. The GFA extension consist of several gears positioned on a row making it possible to perform tightening’s in difficult positions. This project involves the mechanical design and assembly of a gear test rig that the company can leverage for future GFA development assessments. The degree project includes Computer Aided Design (CAD) design drawings of the rig and explanation of component selection necessary to assemble and operate the gear train test rig. The development process of the gear train test rig will be documented and discussed with regards to functionality, tolerance and fit, manufacturing, assembly, and maintenance. The project is divided into three phases, the design and construction phase, the assembly phase, and the test phase. The final design of the gear train test rig consists of several gear modules, allowing flexibility in adjusting the number of gear steps based on the operator's testing requirements. Each gear module is clamped onto a T-slot aluminum plate. The input and output modules are placed in the beginning and at the end of the test rig gear train. The input module is connected to the power source and the output module is connected to the system pneumatic brake. The gear steps can easily be set and rearranged by changing the number of middle modules incorporated to the gear train test rig. To validate the functionality of the assembled test rig, grease test cases have been conducted. Research indicates that power losses occur during gear meshing because of friction between interlocking gear teeth, which in this case will impact the gear test rig efficiency. Studies show that lubrication applied to gears can improve tool performance significantly (Westbroek, Leckner & Olsson, 2023). Test cases were conducted both with no applied grease on gears and with two different greases applied to the gears. These test cases validate the test rig's performance and the effects of different lubrication conditions. The conclusive test results reveal that the comparison between the two different greases did not show any significant difference, although applying grease to the gears enhances the test rig efficiency by nearly 19 %. The conclusive assessment of the constructed test rig's performance reveals that the rig will operate with a 95 % efficiency during two-gear-step test cases.